Effect of Indoleamine 2,3 Dioxygenase Inhibitor on the Cytotoxic Activity of Tumour-infiltrating Lymphocytes - Sarah Le Naour; Anne-Chantal Knol; Marie-Christine Pandolfino; Amir Khammari; Brigitte Dréno (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)